Long-Term Effects of Aluminum and Cadmium on Growth, Leaf Anatomy, and Photosynthetic Pigments of Cotton - VARDAR, FİLİZ; ÖZYİĞİT, İBRAHİM İLKER; AKINCI, ŞENER (TAYLOR & FRANCIS INC, 2013)
Aluminum (Al) and cadmium (Cd) are two elements that contaminate soil in different ways as waste products of some industrial processes and that can be tolerated by some plant species in different concentrations. In this study, growth parameters of leaves and stems (fresh and dry weights, stem lengths, leaf surface area, and lamina thickness), anatomical changes in leaves (lower and upper epidermis, stomata and mesophyll tissue), and photosynthetic pigment contents (chlorophyll a and b, total chlorophyll, and carotenoids) were investigated in cotton (Gossypium hirsutum L. cv. Nazilli 84S), which was treated with Al and Cd for 3 months. Cotton seedlings were grown in greenhouse conditions and watered with Hoagland nutrient solutions, which contained 0, 100, and 200 M aluminum chloride (AlCl3) and cadmium chloride (CdCl2). It was observed that reduced soil pH positively affected many parameters in cotton plants. Aluminum accumulation was greater in leaves than stems while the opposite was true for Cd accumulation. Leaves and stems of cotton plants treated with 100 and 200 M Al and Cd showed slight growth changes; however, high concentrations of Al (200 M) caused significant reductions in leaf area and leaf fresh weight, whereas stem fresh weight decreased with 200 M Cd treatment. Anatomical parameters were mostly affected significantly under both concentrations of Al and Cd solutions (100 and 200 M). The results revealed that the anatomical changes in the leaves varied in both treatments, and the long-term effect of the tested metals did not include harmful effects on anatomical structures. Moreover, the variations could be signals of tolerance or adaptive mechanisms of the leaves under the determined concentrations.
Keywords: Carotenoids; chlorophyll; Gossypium hirsutum L; trace elements; ROOT-GROWTH; STRESS RESPONSES; ALLIUM-CEPA; TOXICITY; LEAVES; PLANTS; WHEAT; CELLS; L.; ACCUMULATION